Studies on in vitro human T cell reactivity to antigens of mycobacterium tuberculosis - Gideon, Hannah Priyadarshini (Division of Medical Microbiology, 2014)
Studies on Mycobacterium tuberculosis (MTB) antigens are important to improve immunodiagnostics and vaccine efficacy. A novel genome based strategy for antigen discovery is to relate what is highly expressed by bacilli in vivo or in vitro, to what is recognized by human T cells as antigens. As hypoxia is a relevant stimulus that MTB encounters in vivo, whole genome based transcriptional profiles of M. tuberculosis subject to prolonged hypoxia (described as the Enduring hypoxic response (EHR) were analyzed, to guide the discovery of novel potential anitgens, by a combined bioinformatic and empirical approach and to determine evidence of infection stage specific recognition.